The Impact of Knowledge Management by Technological Tools and Electronic-means on Academic Staff Performance in Palestinian Universities - Rabayaa, Saed M.; Obaid, Shaher M. (International Review of Management and Marketing, 2019)
This study aims to establish how the management of knowledge through technological and electronic means, impacts the performance of staff within Palestinian universities. Specifically, the study focusses on the West Bank area of Palestine, where 11 universities are located. A total of around 3000 individuals are employed by these universities, and of these, a total of 282 responded to the survey that was used to collect data. Analysis of this data has revealed a positive relationship between the independent and dependent variables that apply. This pattern suggests that the availability of technological and electronic devices does positively affect how staff within universities perform. The study discusses the implications of this and concludes that investment in tools would aid progress within the universities that were considered. Keywords: Knowledge-Management; Technological-Tools & Electronic-Means, academic staff-performance. JEL Classifications: M10, M19, I23 DOI: https://doi.org/10.32479/irmm.7656